Identification of drought tolerant recombinant inbred lines (RILs) based on selection indices in bread wheat - Khare, Vikrant; Pandey, Suneeta; Singh, Sanjay; Shukla, Ravi Shankar (Journal of Cereal Research, 2025)
Water scarcity throughout wheat-growing periods is a major issue in India, therefore breeding methods, as well as the efficient selection approaches for moisture stress conditions are required to retain the level of crop production. In the current study recombinant inbred lines were developed through a donor, WH 730 crossed with recepient MACS 2496. Further segregating generations were advanced through the single seed descent method at Karnal. The F7 and F8 generations of 231 recombinant inbred lines along with five checks were planted in Alpha Lattice design for screening under normal and restricted irrigated conditions. A significant yield reduction was observed under restricted irrigated conditions than the normal irrigated condition during cropping season 2019-20 & 2020-21. Under stress condition significant association was found among yield and selection indices viz., stress susceptibility index (SSI), tolerance index (TOL), mean productivity (MP), stress tolerance index (STI), yield index (YI), drought resistance index (DI), sensitivity drought index (SDI), relative drought index (RDI), yield stability index (YSI) and percentage of yield reduction (PR). Based on selection indices, 22 recombinant lines were identified superior. These selected recombinant inbred lines may be subjected to further evaluation, and also incorporated as donor parents in future hybridization programs. The panels of extreme phenotypic lines were also used to know the location of particular drought-engaged genes and quantitative trait loci.